Analysis of Economic Value Added (EVA) and Market Value Added (MVA) in Assessing the Performance of Sharia Financial Institutions (Case Study at PT Bank Sumut Syariah Tbk) - Kamilah .; Laylan Syafina; Rizka Fadhillah (LPPM UIKA Bogor, 2023)
Financial performance is the result or achievement achieved by the company in a certain period which describes the level of the soundness of the company to assist investors or potential investors in making decisions. Assessment of the company's financial performance using the EVA and MVA methods describes the optimal level of return on wealth for the company and investors. The purpose of this research is to measure the financial performance of PT. Bank Sumut Syariah uses the EVA and MVA methods, to determine the amount of economic added value creation and wealth creation that has been generated by the company for creditors and shareholders. This research was conducted at PT. Bank Sumut Syariah for the 2017-2021 period in period studied, Bank Sumut Syariah experienced an increase and decrease in its operational and finances seen from its annual financial reports. Based on the results of the analysis of the value of financial performance using the EVA method, PT. Bank Sumut Syariah has succeeded in creating a positive EVA value for the company every year. Rp. 623,456 (in millions of rupiah) in 2017, Rp. 496,207 (in millions of rupiah) in 2018 experienced a decrease in EVA value from the previous year, Rp. 537,199 (in millions of rupiah) in 2019 the EVA value again increased, in 2020 Bank Sumut Syariah experienced a decrease in the positive EVA value of Rp. 506,628, in 2021 Bank Sumut Syariah has again succeeded in increasing the positive EVA value of IDR 608,185. Management has succeeded in meeting the expectations of both creditors and shareholders.